Vedibandha of the Garbhagriha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The kumbha (pot) moulding of the vedibandha (basal mouldings) of the Hazareshwar Temple is notable for its depiction of divine figures in the niches, showcasing various gods and goddesses. In the provided image, one can observe Kubera, depicted seated and with four arms. He holds a money bag in his upper arms and a kamandalu (water pot) in his lower left. The top of the kumbha features a carved chaitya (dormer window) arch, a motif commonly found on the moulding of kapotapalika (cyma recta).